IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS ICT UNTUK MENINGKATKAN HASIL BELAJAR SISWA DAN EFEKTIFITAS MEDIA PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Tridelpina Purba, Sumarny; Saragih, Marlindoaman; Lidya, Dinda (Jurnal Metabio, 2024)
This research aims to determine the increase in student learning outcomes and media effectiveness after implementing ICT-based learning media. This research is a quasi-experiment in a pretest-posttest control group design. The research population was 75 students consisting of 3 classes at the Family Education Foundation Middle School for the 2023/2024 academic year. The research sample was 50 students consisting of 2 classes, samples were taken using cluster random sampling techniques. Learning outcomes are measured using a multiple choice test, while media effectiveness is measured using a questionnaire. Furthermore, the data obtained were analyzed using quantitative descriptive by carrying out analysis prerequisite tests and hypothesis testing with a significance level of α = 0.05. The results of this research show that there is a significant increase in the implementation of ICT-based learning media on student learning outcomes with a probability value of 0.001 < 0.05 and tcount (3,474) > ttable (2,010) and it can be concluded that Ha is accepted. H0 is rejected, which means it can be concluded that There is a significant increase in student learning outcomes after implementing ICT-based learning media and the results of this research show that the percentage of media effectiveness is 82% for media experts who can be categorized as effective, 84% for student responses which are also ncluded in the effective category.